Design and experimental analysis of a prototype waterjet facility for cathode ray tube cutting: evidence from a case study. (1st January 2011) - Gamberini, Rita; Rimini, Bianca; Galloni, Luca; Baroni, Andrea
Cathode ray tubes (CRTs) adopted in TV sets and computer monitors represent a consistent portion of waste electrical and electronic equipment (WEEE). In comparison with the recycling of WEEE such as refrigerators or washing machines, the recovery process for CRT containing devices is very difficult. CRTs are composed of four types of glass (panel, funnel, neck and frit seal) with different compositions. Furthermore, dangerous substances are contained within (i.e., lead, barium, strontium and fluorescent dust). Hence, the need to define robust processes for the design and implementation of efficient facilities for CRT cutting arises. This work describes steps guiding the design and the experimental optimal setting of a prototype facility for water-jet cutting of CRTs, in order to obtain recyclable high quality glass. Initially, a version of the cutting facility with manual movement of the cutting tool is set, in order to evaluate expectable cutting results. Subsequently, a detailed setting of automated movement of the cutting tool is carried out, in order to improve the quality of obtainable glass. As a consequence, a water-jet cutting facility which guarantees the cutting of high quality CRTs is finally set and a prototype is implemented.